Sarcopenia influences clinical outcome in hospitalized patients with peripheral artery disease aged 75 years and older - Schmitt, Volker H.; Hobohm, Lukas; Brochhausen, Christoph; Espinola-Klein, Christine; Lurz, Philipp; Münzel, Thomas; Hahad, Omar; Keller, Karsten (Annals of vascular surgery, 2025)
Background - Sarcopenia represents a relevant comorbidity in patients with peripheral artery disease (PAD). However, only few studies exist assessing the clinical burden of sarcopenia in PAD. - Methods - All hospitalizations of patients aged ≥75 years who were admitted due to PAD within 2005-2020 in Germany were included in the study and stratified for sarcopenia. Temporal trends and the impact of sarcopenia on treatment procedures as well as adverse in-hospital events were investigated. - Results - Overall, 1,166,848 hospitalization cases of patients admitted due to PAD (median age 81.0 [78.0-85.0] years; 49.5% female sex) were included, of which 2,109 (0.2%) were coded with sarcopenia. Prevalence of sarcopenia in these patients increased during the observational period from 0.05% in 2005 to 0.34% in 2020 (β 2.61 [95%CI 2.42-2.80], P < 0.001). Sarcopenic PAD patients were more often female (52.1% vs. 49.5%, P = 0.015), obese (6.6% vs. 5.5%, P = 0.021), and revealed higher prevalences of comorbidities (Charlson comorbidity index, 7.00 [6.00-9.00] vs. 6.00 [5.00-7.00], P < 0.001). Sarcopenia was associated with reduced usage of reperfusion treatments (endovascular intervention: odds ratio (OR) 0.409 [95%CI 0.358-0.466], P < 0.001; surgical revascularization: OR 0.705 [95%CI 0.617-0.805], P < 0.001) but higher conduction of amputation (OR 1.365 [95%CI 1.231-1.514], P < 0.001) and higher rates of major adverse cardiovascular and cerebrovascular events (MACCE) (OR 1.313 [95%CI 1.141-1.512], P < 0.001) and in-hospital death (OR 1.229 [95%CI 1.052-1.436], P = 0.009). - Conclusions - Sarcopenia is an under-recognized condition in PAD patients of high clinical relevance causing a crucial disease burden. Awareness of the ailment needs to be increased in daily clinical practice to identify sarcopenia and improve the clinical outcome of this vulnerable patient group.
Auf dem Titelblatt steht am Ende der Verantwortlichkeitsangabe "Mainzand" anstelle von Mainz
Online verfügbar: 19. Oktober 2024, Artikelversion: 12. November 2024
Gesehen am 13.05.2025